ANALYSIS OF THE INFLUENCE OF GRDP, FOREIGN DIRECT INVESTMENT, AND POPULATION DENSITY ON ENVIRONMENTAL QUALITY IN JAVA IN ACHIEVING THE SUSTAINABLE DEVELOPMENT GOALS (SDGS) - Nura Yulianti; Kiky Asmara; Fauzatul Laily Nisa (JURNAL PROFIT, 2025)
This study aims to analyze the effects of Gross Regional Domestic Product (GRDP), Foreign Direct Investment (FDI), and Population Density on environmental quality in Java Island during the period 2014–2024. The research method employed is panel data analysis with a regression approach, covering six provinces in Java as the units of observation. The dependent variable used is the Environmental Quality Index, while the independent variables consist of GRDP, realized FDI, and Population Density. The findings indicate that GRDP has a significant relationship with the Environmental Quality Index, following the pattern of the Environmental Kuznets Curve (EKC). Meanwhile, FDI shows a positive and significant effect on the Environmental Quality Index. Population Density is also proven to exert a negative and significant influence on the Environmental Quality Index. Therefore, synergy among various stakeholders is required to encourage the implementation of environmentally friendly economic concepts. The green economy approach can serve as a foundation for sustainable development, accompanied by population growth control, reduced dependence on fossil energy, and accelerated transition toward renewable energy, which have been incorporated into the SDGs agenda as a pillar supporting the balance between economic activities and environmental sustainability.